2007
DOI: 10.4049/jimmunol.178.3.1845
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone Dose-Dependently Influences Inflammation and Coagulation during Human Endotoxemia

Abstract: The effects of steroids on the outcome of sepsis are dose dependent. Low doses appear to be beneficial, but high doses do not improve outcome for reasons that are insufficiently understood. The effects of steroids on systemic inflammation as a function of dose have not previously been studied in humans. To determine the effects of increasing doses of prednisolone on inflammation and coagulation in humans exposed to LPS, 32 healthy males received prednisolone orally at doses of 0, 3, 10, or 30 mg (n = 8 per gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 43 publications
4
72
1
2
Order By: Relevance
“…These cytokines play a pivotal role in LPS-induced endotoxic shock, and inhibition of the LPSinduced cascade of proinflammatory cytokines is the primary mechanism through which anti-inflammatory molecules confer protection against the lethal effects of LPS administration. [31][32][33] In line with this, we showed that IL-25 pretreatment protected animals from the LPS-induced death. Importantly, the therapeutic effect of IL-25 in this model was associated with no significant change in the production of Th2-and Th17-related cytokines (ie, IL-4 and IL-17A, respectively), thus arguing against the hypothesis that some of the negative effects of IL-25 on the course of LPS-mediated endotoxemia are indeed due to its ability to either promote Th2-or inhibit Th17-associated cell responses.…”
Section: Discussionsupporting
confidence: 82%
“…These cytokines play a pivotal role in LPS-induced endotoxic shock, and inhibition of the LPSinduced cascade of proinflammatory cytokines is the primary mechanism through which anti-inflammatory molecules confer protection against the lethal effects of LPS administration. [31][32][33] In line with this, we showed that IL-25 pretreatment protected animals from the LPS-induced death. Importantly, the therapeutic effect of IL-25 in this model was associated with no significant change in the production of Th2-and Th17-related cytokines (ie, IL-4 and IL-17A, respectively), thus arguing against the hypothesis that some of the negative effects of IL-25 on the course of LPS-mediated endotoxemia are indeed due to its ability to either promote Th2-or inhibit Th17-associated cell responses.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas high concentrations of recombinant IL-10 up to 300 ng/ml are commonly used for in vitro and ex vivo experiments (5,20,28,31,38,59), the in vitro endogenous expression of IL-10 rarely exceeds 1 ng/ml, even when cells are stimulated with high concentrations of LPS (100 -1,000 ng/ml) (24,47). Similarly, endogenous IL-10 concentration is even lower in plasma of humans afflicted with various diseases, such as malaria (15) and human African trypanosomiasis (11), or in healthy males injected with 4 ng/kg LPS (13). We utilized a low, more physiologically relevant concentration of IL-10 (10 ng/ml) to evaluate how it regulates IL-1␤-induced signaling activity in myoblasts.…”
Section: Methodsmentioning
confidence: 99%
“…The volunteers were challenged (at t ϭ 0) with LPS (Escherichia coli LPS, lot G; U.S. Pharmacopeia) as a bolus i.v. injection at a dose of 4 ng/kg body weight as previously described (32)(33)(34). Blood was collected from a cannulated forearm vein directly before LPS administration (t ϭ 0) and at 1, 2, 3, 4, 6, 8, and 24 h thereafter.…”
Section: Subjects and Endotoxemia Modelmentioning
confidence: 99%